Towards a knowledge-hub destination: analysis and recommendation for implementing TOD for Qatar national library metro station - Nur Alah Abdelzayed Valdeolmillos (17714307) (2023)
During the past two decades, Qatar, a developing country, has invested heavily in infrastructure development to address several challenges caused by the rapid urbanization. Qatar has made a significant step toward its urban sustainability vision through the construction of the Doha Metro system. By adopting Transit-Oriented Development (TOD), Qatar is overcoming some urban challenges. TOD promotes compact, walkable, and mixed-use development around the transit nodes, which enhances the public realm through providing pedestrian-oriented and active spaces. Additionally, Qatar aims to transfer to a knowledge-based economy through developing an environment that will attract knowledge and creative human power. Qatar Foundation is taking the lead toward implementing a Knowledge-Based Urban Development (KBUD) through its flagship project: Education City (EC). This study aims therefore to evaluate the integration of TOD and KBUD strategies to leverage the potential of TOD in attracting knowledge and creative economy industries. The selected case study is Qatar National Library (QNL) metro station at the EC in Doha. The study examines the potential of QNL as a destination TOD to enhance the area's mission as a driver for a knowledge-based economy. The methodological approach is based on the analytical concepts obtained from the Integrated Modification Methodology as a sustainable urban design process. The study’s results revealed that void and function, followed by volume, are the weakest layers of the study area's Complex Adaptive System which require morphological modification to achieve sustainability and a knowledge-hub TOD. The study offers recommendations to assist planners and designers in making better decisions toward regenerating urban areas through a knowledge-hub TOD contributing to the spill out of knowledge and creativity into the public realm creating a human-centric vibrant public space adjacent to metro stations. Other Information Published in: Environment, Development and Sustainability License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s10668-023-03118-y